Di Bao : A Guaranteed Minimum Income in China’s Cities? - Chen, Shaohua (World Bank, Washington, DC, 2012)
Concerns about incentives and targeting naturally arise when cash transfers are used to fight poverty. The authors address these concerns in the context of China's Di Bao program, which uses means-tested transfers to try to assure that no registered urban resident has an income below a stipulated poverty line. There is little sign in the data of poverty traps due to high benefit withdrawal rates. Targeting performance is excellent by various measures. Di Bao appears to be better targeted than any other program in the developing world. However, all but one measure of targeting performance is found to be uninformative, or even deceptive, about impacts on poverty. The authors find that the majority of the poor are not receiving help, even with a generous allowance for measurement errors. While on paper, Di Bao would eliminate urban poverty, it falls well short of that ideal in practice.